Conical intersections induced by light: Berry phase and wavepacket dynamics - Halász, Gábor J.; Vibók, Ágnes; Šindelka, Milan; Moiseyev, Nimrod; Cederbaum, Lorenz S. (Journal of physics. B, Atomic, molecular and optical physics, 2011)
Conical intersections (CIs) play an important role in nonadiabatic molecular processes. Characterizing and localizing them is important for describing and controlling electronic energy flow in molecules. It is known that no CI appears in free diatomic systems. In earlier works (Moiseyev et al 2008 J. Phys. B.: At. Mol. Opt. Phys. 41 221001, Sindelka et al 2011 J. Phys. B.: At. Mol. Opt. Phys. 44 045603) it was pointed out that CIs can be formed both by standing and running laser waves even in diatomics. The energetic and internuclear positions of these CIs depend on the laser frequencies, while the strength of their nonadiabatic couplings can be modified by the field intensities. In this work, we calculate the topological or Berry phase of the light-induced CI in the Na2 molecule. The presence of this phase is a clear fingerprint of the laser-induced CI. In addition, we perform a detailed study of the wavepacket propagation and discuss effects which reflect the significant presence of the laser-induced CI.